Synergy of Anaerobic Soil Disinfestation and Trichoderma spp. in Rhizoctonia Root Rot Suppression - Khadka, Ram B.; Miller, Sally A. (Frontiers in Sustainable Food Systems, 2021)
Potential synergy between anaerobic soil disinfestation (ASD) and Trichoderma spp. in suppression of Rhizoctonia root rot in radish was evaluated. A split-plot design with three replications was used; main plots were T. harzianum T22, T. asperellum NT25 and a non-Trichoderma control. Subplots were ASD carbon sources wheat bran, molasses, chicken manure, and mustard greens and two non-amended controls: anaerobic (covered and flooded) and aerobic (not covered or flooded). Carbon sources and R. solani inoculant were mixed with soil, placed in pots and flooded, followed by drenching Trichoderma spore suspensions and sealing the pots in zip-lock bags. After three weeks, bags were removed, soil was aired for one week and radish 'SSR-RR-27' was seeded. Rhizoctonia root rot severity and incidence were lowest in radish plants grown in ASD-treated soil amended with wheat bran, molasses or mustard greens across all Trichoderma treatments. Disease severity was lower in radish plants treated with NT25 than with T22 or the non-Trichoderma control across all ASD treatments, and in radish grown in ASD-treated soil amended with wheat bran plus NT25 compared to ASD-wheat bran or NT25 alone. Rhizoctonia solani populations were significantly reduced by ASD treatment regardless of carbon source, while Trichoderma populations were not affected by ASD treatment with the exception of ASD-mustard greens. The interactions of either Trichoderma isolate and ASD with most carbon sources were additive, while T22 with ASD-molasses and NT25 with ASD-wheat bran interactions were synergistic in reducing disease severity. One interaction, T22 with ASD-chicken manure was antagonistic. Enhancement of ASD efficacy in suppressing soilborne diseases such as Rhizoctonia root rot by additional soil amendment with Trichoderma spp. during the process appears to be dependent on both Trichoderma isolate and ASD carbon source.